Analysis of the Methodologies Used for Quantifying or Setting the Yield Stress of Copper Tailings - Garrido, PA; Diaz, RA (Paste 2009: Twelfth International Seminar on Paste and Thickened Tailings, 2009)
Nowadays the aim of obtaining tailings in the form of consistent slurries is becoming increasingly widespread. Due to this, it is now a must to specify the rheological features of all pulp suspensions with a high solid content. This is particularly relevant when aiming at a process design and optimisation for both the thickening and final disposal of such tailings alike. The specific objective of this paper is the comparison of measurements undertaken with the use of a rotary rheometer and other techniques which are both low cost and easy to implement. The methodologies considered range from rheometry (CR mode), slump tests, Marsh cone and flume. The results obtained indicate that it is feasible to find a relationship between the flow strain readings obtained with the rotary rheometer and the parameters derived from each of the alternative methods considered; as well as the final height of the cone and cylinder in the case of the slump tests, the flow time in the Marsh cone and the standstill angle in the flume tests.